Digital Communication as a Predictor of the Psychological Well-Being of the Older People in the Digital Era - Qoyyimah, Nur Rohmah Hidayatul; Suryani, Cahya; Tantiani, Farah Farida (Jurnal Sains Psikologi, 2024)
The older people in today’s era are non-digital native societies, so adapting to changes in all aspects of life that have been digital-based takes greater effort than individuals under their age. The difficulty of adapting to this digitalization system allows older people to experience negative feelings that affect their psychological well-being. This is correlational quantitative research to investigate further the role of digital media communication on the psychological well-being of older people. The respondents are 55–75 years old, have gadgets, and are used to communicating digitally. A sample of 97 people was selected using a convenience sampling technique. The instrument used is the Indonesian version of the psychological well-being questionnaire and the adapted version of the communication questionnaire through digital media. The results showed that digital communication played a significant role (p < .001) in psychological well-being with an R-squared value of .121. This value means that the digital communication variable can predict the psychological well-being of older people by 12.1%.